Pendampingan Pengembangan Media Pembelajaran dan Publikasi Karya Tulis Ilmiah bagi Guru di SMKN 7 Malang - Cindy Cahyaning Astuti; Akbar Wiguna; Mahardika Dharmawan Kusuma Wardana; Chendi Pirwanto Putra (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2022)
Information Technology (IT)-based learning media is a form of IT utilization that can be used to develop learning media. Teachers are required to be more creative in packaging material in form of learning media. Besides being required to create interactive learning media, teachers are also required to carry out scientific writing publications. Publication of scientific papers can be defined as dissemination of original scientific research results. Publication of scientific papers is carried out as a form of contribution to improving quality of education. The problems experienced by schools as partners for community service activities are that teachers have not been able to maximize IT in the development of learning media and the teacher's low knowledge of procedures for publishing scientific papers, both publications in accredited scientific journals and HKI. The solution offered based on description of the partner's problems that have been described is conducting training on the development of IT-based learning media and publication of scientific papers. Through this training activity, teachers can add insight and skills related to development of IT-based learning media and publication of scientific papers. Based on the results of the training activities, it can be seen that there is an increase in teachers' understanding of development of IT-based learning media and publication of scientific papers based on increased understanding of  six aspects that have been measured.Media pembelajaran berbasis Teknologi Informasi (TI) adalah bentuk dari pemanfaatan TI yang dapat digunakan untuk mengembangkan media pembelajaran. Guru dituntut agar lebih kreatif dalam mengemas materi dalam bentuk media pembelajaran. Selain dituntut untuk membuat media pembelajaran yang interaktif, guru juga dituntut untuk melaksanakan publikasi karya tulis ilmiah. Publikasi karya tulis ilmiah dapat didefinisikan sebagai penyebarluasan hasil penelitian ilmiah bersifat original. Publikasi karya tulis ilmiah dilakukan sebagai bentuk kontribusi pada peningkatan kualitas Pendidikan. Permasalahan yang dialami sekolah sebagai mitra kegiatan abdimas adalah guru belum dapat memaksimalkan TI dalam pengembangan media pembelajaran serta rendahnya pengetahuan guru terhadap tata cara publikasi karya tulis ilmiah, baik publikasi pada jurnal ilmiah terakreditasi maupun HKI. Solusi yang ditawarkan berdasarkan uraian permasalahan mitra yang telah dideskripsikan adalah melakukan pelatihan pengembangan media pembelajaran berbasis TI dan publikasi karya tulis ilmiah. Melalui kegiatan pelatihan ini dapat menambah wawasan dan ketrampilan guru terkait pengembangan media pembelajaran berbasis TI dan publikasi karya tulis ilmiah. Berdasarkan hasil kegiatan pelatihan dapat diketahui bahwa terdapat peningkatan pemahaman guru terhadap pengembangan media pembelajaran berbasis Teknologi Informasi (TI) dan publikasi karya tulis ilmiah berdasarkan peningkatan pemahaman pada enam aspek yang telah diukur.